Comparison of direct radionuclide cystography and voiding cystourethrography in detecting vesicoureteral reflux - (:unkn) unknown (WILEY, 2006)
Fluoroscopic voiding cystourethrography (VCUG) is a widely used imaging test for the diagnosis of vesicoureteral reflux (VUR). However, high gonadal radiation and intermittent imaging are the main disadvantages of VCUG. Direct radionuclide cystography (DRC) has been advocated for the detection of VUR with increased sensitivity and low radiation doses, however, having the disadvantage of providing less anatomical details for urethral evaluation. In this study, DRC has been compared with standard fluoroscopic VCUG for detection of VUR. A total of 41 children (82 kidney ureter units, KUU) aged 1 month-126 months (median, 15 months) were studied sequentially using DRC and VCUG. The indications of VUR studied were urinary tract infection in 29 children, VUR follow up in eight children and antenatal dilatation history in four children. A total of 18 refluxing ureters were detected by DRC, 22 refluxing ureters by VCUG and 14 refluxing ureters by both methods. The two methods were concordant for the detection and exclusion of VUR in 85% of KUU. VUR was missed by VCUG in four KUU (three severe, one mild) whereas VUR was missed by DRC in eight KUU (four grade I, four grade III). There was a good correlation between DRC and VCUG in the evaluation of VUR. DRC provides continuous monitoring and low gonadal radiation exposure. DRC can be used in the diagnosis of VUR as an alternative to VCUG in selected cases.
Keywords: direct radionuclide cystography; imaging studies; urinary tract infection; voiding cystouretrography; ENHANCED DETECTION; CHILDREN